2011
DOI: 10.1038/jid.2010.365
|View full text |Cite
|
Sign up to set email alerts
|

No Formation of DNA Double-Strand Breaks and No Activation of Recombination Repair with UVA

Abstract: Longwave UVA is an independent class I carcinogen. A complete understanding of UVA-induced DNA damage and how this damage is processed in skin cells is therefore of utmost importance. A particular question that has remained contentious is whether UVA induces DNA double-strand breaks (DSBs), either directly or through processing of other types of DNA damage, such as recombination repair of replication forks stalled at DNA photoproducts. We therefore studied activation of the recombination repair pathway by sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 61 publications
3
17
1
Order By: Relevance
“…UVA was originally not expected to be involved in the generation of dsbs due to the relative low photonic energy. This idea was supported by a recent study of Rizzo et al (17) who did interpret their experimental data as being indicative for no dsbs induced in cells exposed towards UVA. Additionally, Cadet and Douki (10) argued that induction of dsbs via clustered ssbs is unlikely, since UVA induces more than twice as much 8-oxo-dG compared to ssbs or alkali labile sites.…”
Section: Introductionsupporting
confidence: 56%
“…UVA was originally not expected to be involved in the generation of dsbs due to the relative low photonic energy. This idea was supported by a recent study of Rizzo et al (17) who did interpret their experimental data as being indicative for no dsbs induced in cells exposed towards UVA. Additionally, Cadet and Douki (10) argued that induction of dsbs via clustered ssbs is unlikely, since UVA induces more than twice as much 8-oxo-dG compared to ssbs or alkali labile sites.…”
Section: Introductionsupporting
confidence: 56%
“…It was shown using the comet assay and the alkaline elution analysis that UVA irradiation of cells gave rise to the formation of alkali-labile sites, mostly strand breaks. It was recently confirmed that UVA radiation, in contrast to earlier suggestions, is not able to generate double strand breaks (114).…”
Section: Uva-mediated Oxidatively Generated Dna Damage In Cellscontrasting
confidence: 41%
“…3c). To confirm that it was UVR-induced DNA damage present in keratinocytes that was blocked by skin-resident T cell supernatants, cultured keratinocyte monolayers were analyzed for γH2AX immunoreactivity (43) following UVR treatment (Fig. 6e).…”
Section: Resultsmentioning
confidence: 99%